Wacana Übermensch Dalam Pandangan Nietzsche Dan Peran Gereja Dalam Pengentasan Kemiskinan Di NTT - Taneo, Rolin Ferdilianto Sandelgus; Nuban Timo, Ebenhaizer I.; de Haan, Arly E. M.; D. Koli, Endang (Litbang STFT Widya Sasana Malang, 2024)
Poverty in East Nusa Tenggara is a serious problem that has been as truggle for the government, the church, and the people of NTT for years. Various ways have been taken to overcome this problem, for example the structure of society that must be changed, reducing excessive spending budgets, access roads to remote areas that must be repaired. Poverty in NTT can be overcome by building a market network. However, specifically in this paper, we will look at the potential of NTT people to be empowered to become superior human beings as Nietzsche thought. Indeed, Nietzsche’s thinking is often taken to the extreme because his critique of Christianity is hard to forgive. However, we see that behind his controversial thinking, there are positive values that we can gain and try to put into practice in the context of poverty in NTT. Therefore, it is very important for us to move away from our views that reject radically his thoughts while trying to learn critically about what is the essence of Nietzsche’s thinking and the extent to which it is relevant to the context of poverty in NTT.